Predicting Attitudes towards Lesbians and Gay Men: The Effects of Social Conservatism, Religious Orientation, and Cultural Humility. Issue 3 (September 2019) - Choe, Elise; Srisarajivakul, Emily; Davis, Don E.; DeBlaere, Cirleen; Van Tongeren, Daryl R.; Hook, Joshua N.
This study explores the role cultural humility plays in attitudes and discrimination towards people identifying as gay or lesbian among religious individuals. Specifically, we explore cultural humility as a possible predictor of less discriminatory attitudes towards lesbians and gay men above and beyond the effects of conservatism and religious orientation. Consistent with prior work, we expected that (a) intrinsic religious orientation, extrinsic religious orientation, and conservatism would be positively related to discriminatory attitudes and (b) that quest religious orientation and cultural humility would be negatively related to discriminatory attitudes. Participants ( N = 231) were recruited through MTurk after the 2016 Pulse Nightclub shooting in Orlando, Florida to understand the attitudes and experiences held by Americans. Participants completed measures of religious orientation, attitudes, and behaviors towards lesbians and gay men, and cultural humility regarding LGBT issues. Results supported the hypothesis that cultural humility predicts less discrimination towards lesbians and gay men beyond conservatism and religious orientation. Results, limitations, and future directions are discussed.